SOCIAL PERSPECTIVES; LEGAL POLICY POST-CONSTITUTIONAL COURT DECISION NO. 46 / PUU-XIV / 2016 CONCERNING IMMORAL PROVISIONOF INDONESIA CRIMINAL CODE - hariansah, Syafri (Faculty of Social and Political Sciences University of Bangka Belitung, 2018)
This paper examines the analysis of Court Decision Number 46 / PUU-XIV / 2016 concerning the application to extend criminal offenses in the Criminal Code (KUHP) related to adultery (Article 284), rape (Article 285), and lewd acts (Article 292). In the ruling, the Constitutional Court rejected the request for all. This verdict ends with differences of opinion among Constitutional Justices. Four of the nine Constitutional Court Justices presented dissenting opinions. Decision No. 46 / PUU-XIV / 2016 is very worthy to be studied in depth, because in its decision, there is a conflict of judges based on different perspectives and methods in answering constitutional issues.